2020
DOI: 10.1590/1982-3533.2020v29n1art03
|View full text |Cite
|
Sign up to set email alerts
|

Inovação e capacidade exportadora: evidências para empresas brasileiras

Abstract: Resumo O objetivo deste artigo é verificar se a inovação das empresas brasileiras tem impactos positivos sobre a probabilidade de exportar e a intensidade de exportação. A amostra é composta por empresas industriais da Pesquisa de Inovação (PINTEC) do Instituto Brasileiro de Estatística e Geografia (IBGE), para os anos de 2003, 2005 e 2008. Foram estimados os modelos Probit, Probit bivariado e Probit Ordenado. Os resultados revelam que a inovação influencia positivamente a propensão a exportar, em especial, qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
2
0
2
Order By: Relevance
“…Regarding technological resources, most of those identified in SLR were present in the exploratory research, like "structure for technical assistance or after-sales abroad", "R&D own structure", and "production processes suitable for international demands". Yet, the "exclusive production process" resource does not appear in the exploratory research, perhaps because in Brazil it is a scarcer resource, considering companies' low technological intensity (Carvalho & Avellar, 2013). On the other hand, only the exploratory research identified resources such as "production structure oriented to sustainability", "technological structure for communication and negotiation with foreign markets", "product's patent in Brazil or abroad", and "technology with added value".…”
Section: Cargo Insurancementioning
confidence: 98%
“…Regarding technological resources, most of those identified in SLR were present in the exploratory research, like "structure for technical assistance or after-sales abroad", "R&D own structure", and "production processes suitable for international demands". Yet, the "exclusive production process" resource does not appear in the exploratory research, perhaps because in Brazil it is a scarcer resource, considering companies' low technological intensity (Carvalho & Avellar, 2013). On the other hand, only the exploratory research identified resources such as "production structure oriented to sustainability", "technological structure for communication and negotiation with foreign markets", "product's patent in Brazil or abroad", and "technology with added value".…”
Section: Cargo Insurancementioning
confidence: 98%
“…Os planos de desenvolvimento da C&T chineses são marcados pelo horizonte de longo prazo e pela ênfase na inovação e desenvolvimento de áreas prioritárias, como pode ser notado na elaboração do "The National Medium-and Long-Term Program for Science and Tecnology Development (2006-2020)" (China, 2006. Esse plano foi um marco, pois sua ênfase na busca de inovações autóctones tinha por fim transformar a China num país baseado em inovação, apontando para as atividades-chave e setores, já que deveriam ocorrer avanços tecnológicos (Cassiolato, 2013).…”
Section: Alguns Apontamentos Sobre As Políticas De Desenvolvimento Deunclassified
“…Este estudo parte de uma perspectiva neoschumpeteriana, assim, considera-se que as diferenças tecnológicas e a capacidade inovativa entre os países são determinantes para a direção e o volume de comércio entre eles com base em três características: a tecnologia depende do nível de desenvolvimento de cada país; há padrões de especialização em setores mais inovadores; e há uma grande importância de instituições, como aquelas destinadas à proteção da inovação Avellar, 2020).…”
unclassified
“…The effects of R&D spending on productivity are due to innovation and its incorporation into the production process (Griliches, 1979;Khan, Salim, Bloch, & Islam, 2017;Mairesse & Robin, 2009;Medda & Piga, 2014;Parisi, Schiantarelli, & Sembenelli, 2006;Wakelin, 2001;Zhang et al, 2011). On the other hand, other studies indicate that gains in productivity and, as a consequence, increases in global competitiveness are not solely related to the efforts made to innovate (Carvalho & Avellar, 2013;Cavalcante & de Negri, 2014;Goedhuys, 2007;Rogers, 2006;Steingraber, 2009). Other factors have also been identified to explain this relationship, such as organizational change, personnel development, cooperation, and the acquisition of machines and equipment, among others.…”
mentioning
confidence: 99%